Turning Heads: The Effects of Face View and Eye Gaze Direction on the Perceived Attractiveness of Expressive Faces. (March 2020) - Ho, Pik Ki; Newell, Fiona N.
We investigated whether the perceived attractiveness of expressive faces was influenced by head turn and eye gaze towards or away from the observer. In all experiments, happy faces were consistently rated as more attractive than angry faces. A head turn towards the observer, whereby a full-face view was shown, was associated with relatively higher attractiveness ratings when gaze direction was aligned with face view (Experiment 1). However, preference for full-face views of happy faces was not affected by gaze shifts towards or away from the observer (Experiment 2a). In Experiment 3, the relative duration of each face view (front-facing or averted at 15°) during a head turn away or towards the observer was manipulated. There was benefit on attractiveness ratings for happy faces shown for a longer duration from the front view, regardless of the direction of head turn. Our findings support previous studies indicating a preference for positive expressions on attractiveness judgements, which is further enhanced by the front views of faces, whether presented during a head turn or shown statically. In sum, our findings imply a complex interaction between cues of social attention, indicated by the view of the face shown, and reward on attractiveness judgements of unfamiliar faces.